Getting students to read for pleasure through the sustained silent reading program in the school library - Gapuz, Micaela Virginia P. (2009)
The researcher believes that the Sustained Silent Reading (SSR) program is as practical way to encourage students to read for pleasure. It is a reading program which regularly allots a certain period of time to students to read anything that is of interest to them. However, since most of the SSR programs in previous researches were conducted in the classroom rather than the library, the researcher experimented with the SSR in library to find out if it was a more effective venue for the said reading program for improving students' attitude towards reading and their library use rather than the classroom. To be able to answer this, the researcher divided the Cornerstone Christian Academy of Quezon City high school students into three groups-Experimental group 1 (those who used their library as the venue for SSR); Experimental group 2 (those who used their classroom as the venue for SSR); and the Control group (those who did not participate in any program).